Nanofluids Flow Over A Stretching Sheet with Convective Boundary Condition - Mustapha, Nur Aimi Salihah; Mansur, Syahira (Enhanced Knowledge in Sciences and Technology, 2022)
It has been proved that nanofluids improve the thermal conduction and convection heat transfer capabilities of base liquids. Nanofluids are a novel type of heat transfer fluid that consists of both a base fluid and nanoparticles. As there has been a surge of interest in studying nanofluid flows in the last few years, this research is regarding a study on the nanofluids flow over stretching sheets with boundary conditions. In this research, the governing equations are transformed from partial differential equations into a set of nonlinear ordinary differential equations using similarity variables. Then, Runge-Kutta-Fehlberg method (RKF45) is used to solve a set of similarity equations that approach the boundary conditions. Five parameters influence the transport of momentum, energy, and concentration of nanoparticles in their respective boundary layers which are the parameters of Brownian motion Nb, thermophoresis Nt, Prandtl number Pr, Lewis number Le, and convection Bi. The impacts of all the parameters on boundary layers for thermal and concentration are depicted graphically. Nb, Nt, and Bi heating all contribute to the thickening of the thermal boundary layer. The concentration layer thickens as Bi enhances, but as Le increases, the concentration layer becomes thinner. The impact of Lewis number on the temperature distribution is minor but Nb, Nt, and Bi causes the local temperature to rise.